Ibn Taymiyyah's Evaluation of Istiḥsān in the Ḥanbalī School of Law - Al-Matroudi, Abdul-Hakim (Islamic Studies, 2008)
This paper is an attempt to outline Ibn Taymiyyah's approach to and treatment of istiḥsān within Aḥmad ibn Ḥanbal's legal theory in addition to that of the early Ḥanbalī jurists. The paper also draws attention to Ibn Taymiyyah's rejection of the claim that Aḥmad ibn Ḥanbal held two conflicting positions with regard to istiḥsān, a notion suggested by some Ḥanbalī jurists; in present author's view, he rather argues that Aḥmad ibn Ḥanbal's two seemingly contradictory positions are in reality referring to different situations of its application because Aḥmad ibn Ḥanbal accepts some types of istiḥsān and rejects others. Aḥmad ibn Ḥanbal's rejection and acceptance was dependent solely on the type of cause upon which the istiḥsān was based. It is also apparent from Ibn Taymiyyah's discussions regarding istiḥsān that it is not an independent source of law in the way that the Qur'ān, Sunnah, consensus and qiyās are. Rather, it is a subsidiary legal principle employed to secure a 'fair' and 'correct' ruling regarding a given question.